(untitled) (Fiep Bulletin - online, 2024)
High-performance sports often place athletes at risk of musculoskeletal symptoms due to various causes. This study focuses on musculoskeletal injuries in high-level basketball players, addressing the most common injuries, their causes, prevention and recovery methods. Furthermore, it highlights the crucial role of physical education professionals in the sporting context. Musculoskeletal symptoms are a frequent challenge in high-performance basketball, including sprains, strains and fractures. These injuries are often attributed to intense, repetitive movements during games and training. Prevention plays a vital role in protecting athletes. This involves adequate training, physical conditioning, use of protective equipment and regular monitoring by healthcare professionals. Treatment is approached through techniques such as physiotherapy, surgery and rehabilitation. The physical education professional plays a fundamental role in preventing injuries, ensuring that athletes are physically prepared and trained appropriately. They can also contribute to post-injury recovery by monitoring progress and adapting training programs. This study was based on relevant literature research, which provided a solid basis for the conclusions presented. Ultimately, this work highlights the importance of prevention and professional support in the management of musculoskeletal injuries in high-performance basketball athletes, highlighting the need for a holistic approach to ensuring athletes’ well-being.